Effectiveness of E-LKPD based on Liveworksheets on Improving Students' Motivation and Learning Outcomes - Wahyuniyati, Ni Made; Suastika, I Nengah; Mudana, I Wayan (CV. Media Inti Teknologi, 2025)
Background of Study: The low motivation and learning outcomes of social studies students at SMP Negeri 2 Marga are problems in the learning process. Through the development of digital technology in the world of education, it is necessary to utilize interactive learning media that are more effective and interesting. One of these media is Liveworksheets-based E-LKPD, which allows students to learn independently, interactively, and in real-time.Aims and scope of the paper: This study aims to analyze the effectiveness of using Liveworksheets-based E-LKPD in improving social studies motivation and learning outcomes.Methods: The scope of the study focused on students of SMP Negeri 2 Marga. This study used a quantitative method with a developmental research design. The subjects of the study were students of SMP Negeri 2 Marga class E. The research instruments included a learning motivation questionnaire and a learning outcome test. The data analysis method used quantitative descriptive statistical techniques with an average formula.Results: The results showed that students' learning motivation increased on average from 76 to 81 with classical completeness of 78% to 91%. Students' social studies learning outcomes increased from 74 to 85 with classical completeness of 72% to 94%. Based on the increase in pre-test and post-test results, it can be concluded that Liveworksheets-based E-LKPD is effective in social studies learning.Conclusions: Thus, Liveworksheets-based E-LKPD can be an alternative interactive, interesting, and appropriate learning media for the problems experienced at SMP Negeri 2 Marga.